On the Hybrid Power Mean of Two-Term Exponential Sums and Cubic Gauss Sums - Shaofan Cao; Tingting Wang (Journal of Mathematics, 2021)
In this paper, an interesting third-order linear recurrence formula is presented by using elementary and analytic methods. This formula is concerned with the calculating problem of the hybrid power mean of a certain two-term exponential sums and the cubic Gauss sums. As an application of this result, some exact computational formulas for one kind hybrid power mean of trigonometric sums are obtained.